Methodological Innovation in Teaching: a clipping from the conceptions of teachers of a federal institute (Research, Society and Development, 2020)
The study is the result of an investigation on Methodological Innovation in Teaching (EML), this research was based on the teaching action of teachers of the Federal Institute of Education, Science and Technology of Ceará (IFCE) with the objective of seeking pedagogical practices and their impacts on education. As theorists, reflections were used that gravitate towards methodological innovation, curriculum, training and identity of teachers. The study used for collection two stages: 1) a section of question 10 (Q10) of the questionnaire applied to 107 research subjects and 2) analysis of two interviews analyzed in the light of qualitative research, using the microanalysis method. The results indicate for advances of IFCE teachers in relation to the potentialities of the use of methods thought from the current context, since the classes become more interactive and with greater student activity, besides establishing a relationship between students, teachers and content. Throughout the research, the teaching concern was also registered in creating strategies with active methodologies that simulate the professional environment, in which the student will be inserted, as well as include in their practices based on the contexts of the students.